(untitled) - Haile Marriam Kahssey (Geneva, Switzerland, 1998)
This book takes a serious look at what community health workers do. It describes both their successes and their failures, and it examines those elements - attitudes, management and structure, and resources - that can make or break a community health worker programme. The question posed in this book is not whether community health workers have a future, but rather how the knowledge and abilities of these grass-roots health workers can be used most effectively in a situtation social and economic change and against a background of market-oriented health sector reform
Keywords: health promotion,medical care,public health